Effect of exposure to stress conditions on propidium monoazide (PMA)-qPCR based Campylobacter enumeration in broiler carcass rinses. (June 2015) - Duarte, A.; Botteldoorn, N.; Coucke, W.; Denayer, S.; Dierick, K.; Uyttendaele, M.
Abstract: Campylobacter quantification by qPCR is unable to distinguish viable vs . dead cells in contrast to the culture-based ISO 10272-2 reference method. Propidium monoazide (PMA) has been used to overcome this disadvantage. A Campylobacter PMA-qPCR enumeration method was evaluated for its consistency and compared to the culture-based enumeration for both artificially and natural contaminated broiler carcass rinses. The PMA effect was further evaluated on stressed cells. Five conditions, commonly encountered during the slaughter process and storage (acid, heat, cold, oxidation and freezing), were inflicted to the broiler carcass rinses artificially contaminated with Campylobacter jejuni or Campylobacter coli . A better correlation between the reference method and the qPCR enumeration was obtained when PMA was used. The two cultured-based methods used showed a significant CFU reduction for heat, cold and acid stresses although the PMA-qPCR enumeration showed that viable bacteria were underestimated. Freezing showed the highest reduction effect, while the reduction extend was also overestimated by the microbiological enumeration procedure. Exposure to a mild oxidative stress was the only stress condition applied at temperatures permitting adaptation of Campylobacter and did not lead to either reduction in CFU nor in the PMA-qPCR signal. Highlights: Enumeration with PMA overcomes the culture-based underestimation when cells are stressed. Freezing was a deadly stress to Campylobacter . Freezing broiler meat will diminish public health risk.